Fluid bolus therapy. Issue 5 (October 2015) - Carsetti, Andrea; Cecconi, Maurizio; Rhodes, Andrew
<x xml:space="preserve">Abstract</x> Purpose of review When a condition of hypoperfusion has been identified, clinicians must decide whether fluids may increase blood flow or whether other therapeutic approaches are needed. For this purpose, several tests and parameters have been introduced in clinical practice to predict fluid responsiveness and guide therapy. Recent findings Fluid challenge is the gold standard test to assess the preload dependence of the patients. Moreover, several parameters and tests avoiding fluid administration are now available. Pulse pressure variation and stroke volume variation are based on heart–lung interaction and can be used to assess fluid responsiveness. These parameters have several limitations and can really be used in a limited number of critically ill patients. End-expiratory occlusion test and passive leg raising have been proposed to overcome these limitations. The aim of resuscitation is to increase blood flow and perfusion pressure. Dynamic arterial elastance has been recently proposed to predict the pressure response after fluid challenge in preload-dependent patients. Finally, the effects of volume expansion of hemodynamic parameters do not necessarily reach the microcirculation, which should also be assessed. Summary Nowadays, several parameters are available to assess fluid responsiveness. Clinicians need to know all of them, with their limitations, without forgetting that the final aim of all therapies is to improve the microcirculation.